2020
DOI: 10.12701/yujm.2020.00171
|View full text |Cite
|
Sign up to set email alerts
|

Drug selection for sedation and general anesthesia in children undergoing ambulatory magnetic resonance imaging

Abstract: The prevalence of magnetic resonance imaging (MRI) for diagnosing and monitoring a wide range of disease in children continues to expand with the efficacy benefit of providing high-resolution images of tissue anatomy and quantitative function and the safety advantage of a lack of ionizing radiation [1,2]. Aspects of MRI scans such as loud noises, confined bore of the magnet, and the required immobility to prevent motion artifacts are the causes of anxiety and barriers to successful performance of the procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 83 publications
(118 reference statements)
3
20
0
Order By: Relevance
“…In our study, 0.4% of patients vomited during the procedure, and 3.4% reported gastrointestinal upset in the 24-h post-sedation survey. This value was lower than that of adverse events observed with oral chloral hydrate and pentobarbital ( 30 ). A wide distribution was observed during the time to resume normal activities in the survey.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our study, 0.4% of patients vomited during the procedure, and 3.4% reported gastrointestinal upset in the 24-h post-sedation survey. This value was lower than that of adverse events observed with oral chloral hydrate and pentobarbital ( 30 ). A wide distribution was observed during the time to resume normal activities in the survey.…”
Section: Discussionmentioning
confidence: 56%
“…The success rates of other traditional non-parenteral sedatives in MRI sedation were 86.7% for chloral hydrate in children aged 0 to 10 years ( 27 ), 67% for pentobarbital in children aged 8 months to 8 years ( 28 ), and 59% for midazolam in children aged 1 to 7 years ( 29 ). A previous study revealed that the success rate of dexmedetomidine sedation varied with age, weight and disease ( 30 ). In the current study, we have shown that history of sedation failure was the only risk factor contributing to sedation failure and this finding was consistent with Liu’s study on intranasal dexmedetomidine–ketamine combination ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In paediatric imaging, reduced MRI scanning times would not only allow for more studies to be performed per day, but also contribute to reduced motion artefacts by a less co-operative child 23 and could reduce the need for general anaesthesia and its associated risks. 24 A variety of AI-assisted techniques are being assessed, 25,26 but have predominantly included training a neural network to learn relationships between zero-filled k-space data and those of fully sampled k-space data for a particular study type; thereby allowing for interpolation of missing data in future unseen studies (e.g., in adult brain imaging) 21,27 ; and also by using neural networks to remove aliasing from under-sampled real-time MR data to enhance image reconstruction times (e.g., used in MRI reconstruction of congenital heart diseases in children). 28 In this technique, deep learning artefact suppression reconstructions were reportedly over five times faster than conventional (compressed sensing) image reconstruction methods.…”
Section: Mri Scanning and Image Qualitymentioning
confidence: 99%
“…Due to their anatomical and physical characteristics, children are vulnerable to side effects of sedatives, such as airway obstruction, apnea, and hypotension. For successful completion of procedures without the side effects of sedatives, an appropriate selection of sedatives and determination of dosage are crucial [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%